Unveiling polysomal long non-coding RNA expression on the first day of adipogenesis and osteogenesis in human adipose-derived stem cells - Bonilauri, Bernardo (2024)
This work was funded by CNPq PROEP/ICC Grant 442353/2019-7. B.B. received a fellowship from Fiocruz, and B.D received a fellowship from CNPq.